2019–2020 Florida Citrus Production Guide: Useful Telephone Numbers - Frederick M. Fishel (EDIS)
This 1-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Frederick M. Fishel and published by the Agronomy Department, March 2019.